Day 4 Thu, April 27, 2017 2017
DOI: 10.2118/188125-ms
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Polymer for Improved Sweep Efficiency in High Temperature High Salinity Carbonate Reservoirs: Linear X-Ray Aided Flood Front Monitoring

Abstract: Polymer flooding is one of the most commonly used techniques to improve oil recovery; however its application is dependent on the technical and economic feasibility along with the knowledge of the risks involved. The presented work is focused on quantifying the uncertainties affecting the mobility of injected fluid in polymer flooding along with a sensitivity analysis of influential parameters. Initially, a coreflooding experiment on carbonate core sample is performed using partially hydrolyzed polyacrylamide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The cumulative oil recovery from volumetric production and in situ saturation was 62% and 64%, respectively. This margin error is expected from the laboratory data and could be as a result of inaccuracy when taking manual readings (Hashmet et al 2017b).…”
Section: Core Flooding Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The cumulative oil recovery from volumetric production and in situ saturation was 62% and 64%, respectively. This margin error is expected from the laboratory data and could be as a result of inaccuracy when taking manual readings (Hashmet et al 2017b).…”
Section: Core Flooding Resultsmentioning
confidence: 95%
“…This is an advanced technology that gives better understanding of fluids performances as well as level of capillary end effect. Core flood experiments were also conducted by Hashmet et al (2017b) to study the effectiveness of a HPAM base polymer on oil recovery in HTHS carbonate reservoirs. Results of the experiments showed that the polymer was effective in enhancing the mobility ratio and was able to produce more oil (Hashmet et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al [ 59 ] observed that the degree of polymer adsorption increases with increasing brine salinity (e.g., NaCl concentration) [ 59 ]. Also, even though the xanthan bio-polymer is capable of tolerating very high salinity conditions, it is afflicted with issues of poor injectivity and bio-degradation [ 60 , 61 , 62 , 63 ].…”
Section: Challenges Associated With Polymer Flooding In Harsh Conditionsmentioning
confidence: 99%
“…Generally, most researchers believe that polymers do not contribute to enhancing oil recovery, but assist in increasing the ultimate recovery [ 28 ]. Some others propose that polymers can contribute to EOR by improving the sweep efficiency [ 29 , 30 ]. Lately, polymers have been used in synergetic applications with other cEOR techniques such as alkali and/or nanoparticle injection seeking to improve R–F/F–F interactions [ 18 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%